2014
DOI: 10.1118/1.4888107
|View full text |Cite
|
Sign up to set email alerts
|

SU‐E‐J‐55: Dosimetric Evaluation of Centrally Located Lung Tumors: A Monte Carlo (MC) Study of Lung SBRT Planning

Abstract: Purpose:To compare dose distributions calculated using the iPlan XVMC algorithm and heterogeneities corrected/uncorrected Pencil Beam (PB‐hete/PB‐homo) algorithms for SBRT treatments of lung tumors.Methods:Ten patients with centrally located solitary lung tumors were treated using MC‐based SBRT to 60Gy in 5 fractions for PTVV100%=95%. ITV was delineated on MIP‐images based on 4D‐CT scans. PTVs(ITV+5mm margins) ranged from 10.1–106.5cc(mean=48.6cc). MC‐SBRT plans were generated with a combination of non‐coplana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 0 publications
1
4
0
Order By: Relevance
“…Other authors [43][44][45][46][47] have presented similar results to our work for different fractionation schemes, where the greatest differences between dose algorithms were found for the smaller lesions, embedded in lung tissue, thus the doses received by the tumour were highly dependent on the size, tissue density and location. In all cases, the dose calculated by PB was higher than that obtained by algorithms with adequate heterogeneity correction as MC or Acuros XB.…”
Section: Discussionsupporting
confidence: 87%
“…Other authors [43][44][45][46][47] have presented similar results to our work for different fractionation schemes, where the greatest differences between dose algorithms were found for the smaller lesions, embedded in lung tissue, thus the doses received by the tumour were highly dependent on the size, tissue density and location. In all cases, the dose calculated by PB was higher than that obtained by algorithms with adequate heterogeneity correction as MC or Acuros XB.…”
Section: Discussionsupporting
confidence: 87%
“…That is due to the lack of electronic equilibrium in the regions near low‐density tissues heterogeneities interface. In our most recent clinical study (18) with 10 lung cancer patients, the mean PTV dose was as high as 13%, on average, when using heterogeneities‐corrected PB algorithm compared to XVMC using same beam configurations, MLCs, and the same number of MUs. However, the volume covered by 5 Gy, 10 Gy, and 20 Gy isodose lines of the normal lung were comparable (within 3.0%), on average, when calculated by heterogeneities‐corrected PB compared to XVMC.…”
Section: Methodsmentioning
confidence: 95%
“…XVMC algorithm accurately predicted both the dose delivered to the isocenter and the dose at the boundaries of tumors whereas PB-hete overestimated the dose at the lung-tumor interfaces due to the lack of electronic equilibrium in the regions near low-density tissues and heterogeneous interfaces. In our most recent clinical study (16,17) using a large cohort of lung SBRT patients, the mean PTV dose was overestimated by 15%, on average, when using PB-hete algorithm compared to XVMC using identical beam configurations, MLCs margins, and total number of MUs. Also, the volume of lung receiving 5 Gy, 10 Gy, and 20 Gy was overestimated by about 3.0%, on average, when calculated by PB-hete compared to XVMC.…”
Section: Xvmc Algorithm and Clinical Validationmentioning
confidence: 99%
“…Our own initial clinical experience (15,16,17) on validating and implementing iPlan XVMC algorithm using QUASAR (Modus Medical Devices Inc., London, Canada) phantom study has demonstrated an excellent agreement (within ± 2%) between doses calculated using XVMC versus ion chamber measurements for 6 MV-SRS beams in heterogeneous lung equivalent material. In our phantom study, (15) the dose difference between PB-hete and measured value was as large as 9%.…”
Section: Xvmc Algorithm and Clinical Validationmentioning
confidence: 99%
See 1 more Smart Citation